Pengaruh Media Sosial Instagram dan Review Terhadap Jumlah Penjualan di Bull’s Coffee Jimbaran - Yatami, Ni Komang Dewi; Darmita, Made Yudi; Dewi, Desak Made Purnama (Universitas Triatma Mulya, 2022)
The problem raised in this study is whether Instagram social media (X1) and reviews (X2) have an effect on Sales (Y) at Bull's Coffee Jimbaran. How big is the influence of social media Instagram (X1) and reviews (X2) on sales (Y) at Bull's Coffee Jimbaran? The population in this study amounted to 100 people. The data analysis techniques used were the validity test, reliability test, classical assumption test, multiple linear regression analysis, T-test, and F test. The analysis results showed the regression model Y = 11.628 + 0.266X1 + 0.276X2. The conclusion obtained is that social media Instagram (X1) partially has a positive and significant influence on sales (Y) at Bull's Coffee Jimbaran which shows b1X1 which has a positive value. Both reviews (X2) partially have a positive and significant effect on sales (Y) in Bull's Coffee Jimbaran employees, this can be seen in the positive b2X2 coefficient, the three data used prove social media Instagram (X1) and reviews (X2) together have a positive and significant effect on sales (Y).